Sexual Harassment and Its Impact on Employees - Christian Wiradendi Wolor; Datu Razali Datu Eranza; Mahmoud Ali Rababah; Ahmad Nurkhin; Eka Ary Wibawa (Horizon Research Publishing, 2024)
Sexual harassment remains a prevalent type of mistreatment of employees that frequently transpires within the confines of the workplace. The present study endeavors to address the lacuna in prior research and examine the effects of sexual harassment on employee depression, employee satisfaction, and turnover intention. The research employs a quantitative methodology utilizing structural equation modeling (SEM) to scrutinize the gathered data. The study's sample comprises 406 employees who have encountered incidents of sexual harassment in Indonesia. The SmartPLS 3 program was utilized to analyze questionnaires that were distributed to 406 employees via Google Forms. The results show that sexual harassment affects depression (p = 0.000), sexual harassment does not affect job satisfaction (p = 0.209), depression affects job satisfaction (p = 0.001), depression affects turnover intention (p = 0.000), and job satisfaction affects turnover intention (p = 0.001). The implication of this research is that organizations must take action to prevent sexual harassment in the work environment and reduce its negative effects by making sexual harassment prevention training and rules related to sexual harassment.